Evaluation Of Strategies as the Paramount Of the Central Bank Of Nigeria's New Naira Note Policy. - Sulaiman, T.H; Abalaka, J.N; Ajiteru, S.A.R (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
The objective of this study is to empirically assess the tactics that the CBN of Nigeria has implemented as the key component of the new naira note policy. The research employed a survey design with a sample size of about fifty (50) responders, comprising accountants and auditors from ten (10) ministries chosen from the Federal Capital Territory (FCT) of Abuja, Nigeria. At the 5% significant level, the hypotheses are tested using analysis of variance (ANOVA). The study's conclusions showed a strong association between forensic accounting and the litigation support service provided by Nigerian courts, as well as the effectiveness of forensic accounting in the country's public sector in identifying fraud. In a similar vein, the CBN of Nigeria uses techniques and policies that work well to stop fraud. Therefore, the study suggests that the public sector implement a continuous improvement in the internal control officers responsible for their acts. It should be mandatory for forensic accountants to receive the necessary training in forensic accounting techniques. In order to lower the prevalence of fraudulent activities in Nigeria, public sector employees should also embrace honesty, accountability, fairness, and objectivity as fundamental moral obligations. This study contributes to the existing literature by highlighting the critical role of forensic accounting in enhancing transparency and accountability within the Nigerian public sector, ultimately fostering a more robust financial environment.